Mengkritisi Teologi Sekularisasi - Sonny Eli Zaluchu (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2018)
The theology of secularization was a product of a changing age that was triggered by a shift in philosophical thought at the time of enlightenment. Rationalism put human hegemony over dogmatic issues so that theology also ought to be able to answer a changing need for the postmodern era. This article aimed to show a reflection presented by secularisation theology in post-liberalism. The method used was descriptive historical, to explain the theology of secularization in the context of changes and needs of modern humans until today. The conclusion is that secularization theology is an actualization of modern thought that seeks to apply the values of Christianity in the context of a wider world, independent of its religious and dogmatic hegemony.AbstrakTeologi sekularisasi merupakan produk dari sebuah perubahan jaman yang dipicu oleh pergeseran pemikiran filsafat pada masa pencerahan. Rasionalisme mengembalikan hegemoni manusia di atas persoalan dogmatis, sehingga teologi juga harus dapat menjawab sebuah kebutuhan jaman yang sedang menuju ke arah posmodern. Artikel ini bertujuan untuk menunjukkan sebuah refleksi yang dihadirkan oleh pemikiran teologi sekularisasi pada masa post-liberalisme. Metode yang digunakan adalah deskriptif historis, untuk menjelaskan tentang teologi sekularisasi pada konteks perubahan dan kebutuhan manusia jaman modern hingga saat ini. Sebagai kesimpulan, teologi sekularisasi merupakan aktualisasi pemikiran modern yang mencoba menerapkan nilai-nilai kekristenan dalam konteks dunia yang lebih luas, yang terlepas dari hegemoni agama dan dogmatikanya.